Pengaruh Tingkat Pendidikan, Pengetahuan Zakat, Dan Religiusitas Terhadap Kepatuhan Dalam Membayar Zakat Industri Di Kabupaten Jepara - Wahyuningsih, Fitriana; Anwar, Aan Zainul (Jurnal Iqtisaduna, 2025)
This study aims to analyze the effect of education level, zakat knowledge, and religiosity on compliance to pay industrial zakat in Jepara Regency. This research uses a quantitative approach with primary data obtained through questionnaires to 100 respondents who are furniture industry players in Jepara. The data collected were analyzed using SPSS version 25 software, by applying multiple linear regression analysis, as well as conducting validity tests, reliability tests, classical assumption tests, and hypothesis testing. The level of education is measured through the respondent's last level of education, zakat knowledge includes an understanding of the law of zakat and its payment mechanism, while religiosity reflects the level of individual religious beliefs and practices. The results showed that education level, zakat knowledge, and religiosity simultaneously have a significant effect on compliance to pay zakat. Partially, religiosity has the most dominant influence, followed by education level, and zakat knowledge. This study confirms the importance of improving education, counseling on zakat, and strengthening religiosity values to increase compliance to pay zakat, especially in the industrial sector. The findings provide practical recommendations for zakat management institutions to use education and religiosity approaches in optimizing zakat potential in Jepara Regency.